Modal-Expansion Analysis of Multiple Monopole Antennas - Quanxin Wang; Zhongxiang Shen; Erping Li (International Journal of Antennas and Propagation)
The modal-expansion method is employed to analyze an array of multiple monopole antennas. A perfectly conducting plate is introduced at the top of the monopole array to facilitate the modal-expansion analysis. Expansion coefficients in the field expressions are found by enforcing continuity conditions of the tangential field components across the regional surfaces. Cylindrical function's addition theorem is employed to realize the transformation of field expressions in different coordinate systems. Numerical results for the S-parameters of a two-monopole antenna are presented and they are in good agreement with experimental ones. Also examined is the effect of the distance between two monopoles on the antenna's mutual coupling and radiation pattern. A four-monopole antenna is studied for its beam-steering capability and simulated results for its radiation properties are compared with those obtained by high frequency structure simulator (HFSS).